Anemia in pregnancy and its associated factors: A study from Eastern Nepal (Nepal Journal of Epidemiology, 2014)
Background  Anemia in pregnancy is responsible for many adverse effects on maternal and fetal outcome. It is the commonest hematological disorder accompanying pregnancy. Prevalence of anemia among pregnant women is fairly high worldwide, especially in developing countries. A research finding published by World Health organization revels that the prevalence of anemia among pregnant women in developing countries averages 56% (ranging between 35 to 100%). Though Nepal has decreasing trend of prevalence of anemia, it is still high (42% in 2006). Identifying the associated factors which are responsible for the development of anemia during pregnancy would be of great help in mitigating the burden to some extent. Ojective of the study was to find out the pattern of anemia and associated risk factors for anemia during pregnancy. Materials and Methods A cross-sectional study was conducted in VDC named Hansposa.  Door to door survey was carried out to collect data using pre-designed questionnaires. Ante-natal check-ups were provided with analysis of hemoglobin levels, in every individual of study population, using conventional Shali's method. Chi-square test was applied, where applicable. Results Altogether 249 pregnant women were included in the study. The proportion of anemia was found to be 46.6%, the cases of mild anemia, and moderate anemia were 51.0% and 49.0% respectively. Risk factors includes: history of complications during previous pregnancy (P